The Collaborative Economy in Action: Context and Outline of Country Reports - Andrzej Klimczuk; Vida Česnuitytė; Gabriela Avram (The Collaborative Economy in Action: European Perspectives, 2021)
The term collaborative economy (CE) itself is relatively new, and according to the European Commission, the term is used interchangeably with the term sharing economy (SE). The term SE was frequently used when early models, such as Airbnb or ZipCar, appeared and gained popularity, especially in the United States, but it was afterwards substituted with the term CE in the European contexts. The country reports in this collection often use the two terms interchangeably, further illustrating the fact that a generally agreed definition is still missing. However, the ambition driving the term CE is to create specific European economic models with greater emphasis on the community's involvement. In Europe, it is still the case that the definition of the CE and SE remains fuzzy, including both non-profit and for-profit models, supported by both monetary and non-monetary exchanges among participants. The phenomenon is complex, covering various fields of activity, as well as operating at various levels, ranging from the international to the national, regional, and local. Some definitions focus mostly on sustainability, while others highlight technological and financial aspects and business models specific to the phenomenon. This chapter is organized as follows. First, a short overview of the basic theoretical approaches to CE is presented. Further, the structure of the book is discussed in detail, and the text closes with a summary.
Keywords: D83; D16; Z18; 330; Collaborative Economy; Shared Consumption; Sharing Economy; Platform Capitalism; Legal Regulations; Fair Economy